PbCl2-assisted film formation for high-efficiency heterojunction perovskite solar cells. Issue 1 (22nd December 2015) - Chen, Si; Yu, Xiao; Cai, Xin; Peng, Ming; Yan, Kai; Dong, Bin; Hu, Hsienwei; Chen, Buxin; Gao, Xue; Zou, Dechun
Abstract : PbCl2 is used as an additive to assist perovskite film formation in a two-step sequential deposition process and the device achieved an average efficiency enhancement of approximately 30% compared to the control group. Abstract : In this work, PbCl2 is used as an additive to assist organolead trihalide perovskite film formation in a two-step sequential deposition process. PbCl2 inhibits PbI2 crystallization and contributes to the full conversion of PbI2 and enhanced perovskite film morphology control. Cl − incorporation into the perovskite improves charge transport within the film, as confirmed by the resulting prolonged photoluminescence lifetime observed. A reaction temperature of approximately 50 °C between the PbI2 /PbCl2 film and CH3 NH3 I isopropanol solution is essential for synthesizing high-performance perovskite solar cells. Addition of PbCl2 results in a perovskite solar cell energy efficiency of 14% and achieves an average efficiency enhancement of approximately 30% compared with that obtained from the control group.